Constructing a National Sample of Cities (Advanced Level) - Lehmann, Susan; Schultz, Norah (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Below are the additional parameters that can be used to make this Exercise 2.2 more complex. If you are unfamiliar with the concepts of mean, medium, and mode, you may wish to read the beginning of Exercise 3.1 before beginning this exercise.